Nutritional evaluation and human health-promoting potential of compounds biosynthesized by native microalgae from the Peruvian Amazon - Cobos, Marianela (2020)
A plausible strategy to mitigate socioeconomic problems in the Peruvian Amazon is through the sustainable exploitation of biodiversity resources, such as native microalgae. Several studies worldwide affirm that these microorganisms are excellent sources of higher value products for human nutrition and possess health-promoting biochemicals, but these attributes are unknown for the native microalgae of Peru. Therefore, the aim of this investigation was to evaluate the nutritional and human health-promoting potential of compounds biosynthesized by native microalgae from the Peruvian Amazon. Ten native microalgae strains of the groups cyanobacteria and chlorophyta were cultured in BG-11 medium and their biomass harvested and dried. Standardized methods were then used to determine proximate composition, fatty acids and amino acids composition, antioxidant activity, and total phenolic content. All ten microalgae strains produce primary nutrients, the entire spectrum of essential amino acids, essential fatty acids, and 3 of the 10 microalgae strains produced eisosapentaenoic acid. Additionally, all microalgae strains exhibited antioxidant activities and contained phenolic compounds. In conclusion, native microalgae strains from the Peruvian Amazon analyzed in this study possess the ability to biosynthesize and accumulate several nutrients and compounds with human health-promoting potential.